Analysis of Communication and Leadership Style on Employee Loyalty and Performance - Sameer Seth (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The article Effects of Communication and Leadership Style on Employee Loyalty and Performance is a scientific literature study within the scope of Human Resource Management science. This article aims to build a research hypothesis on the influence between variables, which can later use in further research. In addition, this study aims to see the effect of communication within the organization and leadership style on employee loyalty and performance. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. A descriptive qualitative method, library research, from e-books and open access e-journals. Sourced from previous research that is relevant to this research. The results of this article are: 1) Communication affects Employee Loyalty; 2) Leadership Style influences Employee Loyalty; 3) Communication has an effect on Employee Loyalty; 4) Leadership Style influences Employee Performance; and 5) Employee Loyalty influences Employee Performance.